Effect of the moderate and continuous exercise induced in Rattus norvergicus Wistar - Benavides, Elena R. (2010)
The objective of the present research is demostrate in an experimental way that the continuos moderate exercise has an antioxidant effect reducing the provoked stress. With this clear objective we designed a transversal experiment using case studies with a controlled group using 32 Wistar rats with 25 grams each one and with one month old too. All these rats were distributed in four groups: “A” was the control one, “B” was induced to have stress, “C” was induced to have stress with continuos moderate physical exercise, “D” was under continuos moderated physical exercise. The stress was provoked by ethanol inhalation and some doses of amphetamine (0,5mg/Kg of weight) for 7 days. The rats were under continuos moderated exercises for 7 days. The animals were sacrificed and the antioxidant activity of Superoxido Dismutase (SOD) and Catalasa (CAT) in liver and brain was tested, obtaining the following results: group A, liver: 32,89 x 10-3 UCAT/mg protein & 9.99 x 10-3 USOD/mg protein; brain: 5,99 UCAT/mg protein & 0,37 USOD/mg protein; group B, liver: 27 x 10-3 UCAT/mg protein & 7,63 x 10-3 USOD/mg protein; brain: 4,64 UCAT/mg protein & 0,26 USOD/mg protein; group C, liver: 40,54 x 10-3 UCAT/mg protein & 9,21 x 10-3 USOD/mg protein; brain: 7,97 U CAT/mg protein & 0,37 U SOD/mg protein. Therefore, we conclude that these experimental conditions Group B suffered oxidative stress as a result of treatment, and the Group C achieved a recovery thanks to continuos moderate exercise.